Effectiveness of Psychological First Aid School (PFA-S) synchronous learning on teacher self-efficacy - Rahmatulloh, Ainurizan Ridho; Pratiwi, Ratri; Rahimmatussalisa, Rahimmatussalisa (International Journal of Research in Counseling and Education, 2021)
The education related to the ability in providing social support through PFA is still rarely applied and limited. PFA can provide social support that is needed by the individuals while dealing with the initial stressful situations so they will not experience psychological disorders. In its development, PFA can be applied to a wider context such as in school. Teachers are important figures in providing assistance and giving services to students who have experienced traumatic events. This study is aimed to see the effectiveness of PFA training through synchronous learning on teacher self-efficacy and knowledge. The research method used is one group pre-post design experiment and performed online using Zoom Video Conference. The subjects in this study were middle and high school teachers totaling 37 people (N=37). The data analysis method used is the Wilcoxon matched-paired signed test. The result of this study shows that the subjects experience an increase in self-efficacy after attending PFA training at school. Meanwhile, the level of PFA knowledge in schools for teachers do not increase. PFA online training offers easy access for many people and learning flexibility.